Monetary policy rules in Malaysia, Singapore and Thailand - Tan, Chai Thing; Mohamed, Azali (Bank Indonesia Institute, 2020)
This paper investigates whether monetary policies in Malaysia, Thailand and Singapore are best represented by either the Taylor rule or the augmented Taylor rule. It finds that the augmented Taylor rule, which incorporates the exchange rate and government spending, best represents monetary policies in these countries. The results show that past inflation and the output gap play a role in the monetary policy reaction function in Malaysia and Thailand. The results further show a strong preference towards interest rate smoothing, government spending, and the exchange rate by the central banks.